ANALISIS PROSES PEMBELAJARAN MATA DILKAT GAMBAR DASAR TEKNIK SISWA KELAS 1 JURUSAN TEKNIK BANGUNANSMK NEGERI 2 PAYAKUMBUH - 646-652 , Ulfa Rahmi (Universitas Negeri Padang, 2015)
ABSTRACT Forconductingstudythe teacher is notonlypreparethemselvesphysicallyandmentally, but they also prepare the scenarioorthe Rencana Proses Pembelajaran(RPP). Thisstudyaimstoanalyze thelearning processin the classroomwithlesson planscreated byteachers.The type of thisresearchisdescriptive. Populationin this studyis thefirstclassof studentsmajoring inconstructionengineeringandthe studysamplewas takenbyrandom sampling techniquewith atotal sample of83students.The type of datainthisresearchisprimary dataobtaineddirectlyfromobservationsusingthe observation sheetandsecondary dataobtainedfromschoolrecordsrelated tothe number of studentsin that class. Data analysis techniquesimplementationprocessof learningis donetoanalyzethe learningprocesswith descriptive analysistechniquewhichanalyzesthe implementationof learningin accordancewithlesson planscreated byteachersandtranslatedin narrative form.The results ofthe analysis shows that the learning process is good categories and suitable with RPP, percentage of students attended the TGB, TKK and TKB 66.66% and 69.11%, 70.59% and 75.05%, 70.26% and 69.28% for 1st class and 2nd class respectively for each subject. Keywords: Rencana Proses Pembelajaran